Structure and Dynamics of the gp120 V3 Loop That Confers Noncompetitive Resistance in R5 HIV-1JR-FL to Maraviroc - Yuan, Yuzhe; Yokoyama, Masaru; Maeda, Yosuke; Terasawa, Hiromi; Harada, Shinji; Sato, Hironori; Yusa, Keisuke (PLOS ONE, 2013)
Maraviroc, an (HIV-1) entry inhibitor, binds to CCR5 and efficiently prevents R5 human immunodeficiency virus type 1 (HIV-1) from using CCR5 as a coreceptor for entry into CD4+ cells. However, HIV-1 can elude maraviroc by using the drug-bound form of CCR5 as a coreceptor. This property is known as noncompetitive resistance. HIV-1V3-M5 derived from HIV-1JR-FLan is a noncompetitive-resistant virus that contains five mutations (I304V/F312W/T314A/E317D/I318V) in the gp120 V3 loop alone. To obtain genetic and structural insights into maraviroc resistance in HIV-1, we performed here mutagenesis and computer-assisted structural study. A series of site-directed mutagenesis experiments demonstrated that combinations of V3 mutations are required for HIV-1JR-FLan to replicate in the presence of 1 µM maraviroc, and that a T199K mutation in the C2 region increases viral fitness in combination with V3 mutations. Molecular dynamic (MD) simulations of the gp120 outer domain V3 loop with or without the five mutations showed that the V3 mutations induced (i) changes in V3 configuration on the gp120 outer domain, (ii) reduction of an anti-parallel β-sheet in the V3 stem region, (iii) reduction in fluctuations of the V3 tip and stem regions, and (iv) a shift of the fluctuation site at the V3 base region. These results suggest that the HIV-1 gp120 V3 mutations that confer maraviroc resistance alter structure and dynamics of the V3 loop on the gp120 outer domain, and enable interactions between gp120 and the drug-bound form of CCR5.